Women's Maternal Experiences in Canadian Stepfamilies: An Exploratory Study. Issue 6 (17th August 2016) - Gosselin, Julie; Gosselin, Natasha
ABSTRACT: This study fills an important gap in the motherhood literature by exploring the experience of maternal attachment in women mothering in stepfamilies, and how it relates to their sense of competence as a (step-)parent. Forty-three Canadian women living in stepfamilies completed a series of self-reported measures on their (step)maternal experience. Results enabled us to create a portrait of the maternal experience of women mothering in stepfamilies through measures of coparenting satisfaction, adult attachment style, sense of parenting competence, and the overall quality of the relationship with the children in their care; and to predict the quality of maternal relationship among 3 different mothering contexts (e.g., biological children born in current union, biological children born in a previous union, and stepchildren).